(untitled) (Książnica Śląska, 2025)
The article recalls the figure and work of an outstanding graphic artist and caricaturist, Kazimierz Grus, who was associated with the press of Upper Silesia in the years of the plebiscite and who later supported the political faction of Wojciech Korfanty before the parliamentary election in 1928 and in the post-election period (1929–1930). The author of the paper described drawings of Grus published in the daily “Polonia” and in two Katowice editions (1928 and 1929) of the satirical magazine “Szczutek”, of which he was the editor-in-chief. Some of these drawings are in a unique, original album preserved in the graphic collections of the Silesian Library. The contacts of the artist with the Silesian press were also mentioned, including the post-war „Kocynder” and the weekly “Panorama”.